Morrow, Reiff, Receive 2013 Space Physics and Aeronomy Richard Carrington Awards: Citation for Cherilynn Ann Morrow. Issue 33 (19th August 2014) - Lopez, Ramon
<x xml:space="preserve">Abstract</x> The Space Physics and Aeronomy Richard Carrington (SPARC) Education and Public Outreach Award for Cherilynn Morrow recognizes years of pioneering work on behalf of the space science community in the area of education and public outreach (E/PO).